Photovoltaic Thermal (PV/T) Collectors: A Review - Charalambous, P. G.; Kalogirou, Soteris A.; Maidment, Graeme G.; Karayiannis, Tassos (My University, 2004)
An extensive amount of research on PV-thermal collectors has been carried out over the last 25 years. This paper aims at presenting a review of the most available literature on PV/T collectors. The review is presented in a thematic way, in order to enable an easier comparison of the findings obtained by various researchers, especially on parameters affecting PV/T performance (electrical and thermal). The review covers analytical and numerical models, simulation and experimental work and qualitative evaluation of thermal/electrical output.
Keywords: Review; Literature; PV/T collectors; PV/T performance